Dynamic Changes in Uterine NK Cell Subset Frequency and Function Over the Menstrual Cycle and Pregnancy - Whettlock, Emily M.; Woon, Ee Von; Cuff, Antonia O.; Browne, Brendan; Johnson, Mark R.; Male, Victoria (Frontiers in Immunology, 2022)
Uterine Natural Killer cells (uNK) play an important role in promoting successful pregnancy by regulating trophoblast invasion and spiral artery remodelling in the first trimester. Recently, single cell RNA sequencing (scRNAseq) on first trimester decidua showed that uNKs can be divided into three subsets, which may have different roles in pregnancy. Here we present an integration of previously published scRNAseq datasets, together with novel flow cytometry data to interrogate the frequency, phenotype and function of uNK1-3 in seven stages of the reproductive cycle (menstrual, proliferative, secretory phases of the menstrual cycle; first, second, third trimester; and postpartum). We found that uNK1 and -2 peak in the first trimester, but by the third trimester the majority of uNK are uNK3. All three subsets are most able to degranulate and produce cytokines during the secretory phase of the menstrual cycle and express KIR2D molecules, which allow them to interact with HLA-C expressed by placental extravillous trophoblast cells, at the highest frequency during the first trimester. Taken together, our findings suggest that uNK are particularly active and able to interact with placental cells at the time of implantation, and that uNK1 and 2 may be particularly involved in these processes. Our findings are the first to establish how uNK frequency and function changes dynamically across the healthy reproductive cycle. This serves as a platform from which the relationship between uNK function and impaired implantation and placentation can be investigated. This will have important implications for the study of subfertility, recurrent miscarriage, pre-eclampsia and pre-term labour.